Square Kilometre Array—India Consortium: Education and Public Outreach - Ramanujam N.M.; Dutta P.; Kavila I.; Chakraborty M.; Dhurde S.; Hota A.; Konar C.; Oberoi D.; Pandey-Pommier M.; Rao M.S. (My University, 2025)
This paper presents a report on the activities and the proposed action plan of the Education and Public Outreach Working Group (EPO WG) of Square Kilometre Array–India Consortium (SKAIC). Details of a set of flagship programs as well as supporting activities are presented, in consonance with the scale of India’s involvement in Square Kilometre Array Observatory (SKAO), as well as the educational and science literacy contexts in the country. Ongoing independent EPO activities by some of the member institutions are also included. © 2023, Indian Academy of Sciences.